Peran Manajemen Pendidikan dalam Meninggatkan Student Wellbeing SDN Pleburan 01 - Jati, Ratih Pramudya (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Student wellbeing is a very important aspect in the context of education. School education management has a significant role in improving student welfare. The purpose of this study is to explain the role of education management in improving student welfare through a descriptive qualitative approach. The research method used involved interviews with school principals, teachers, school staff, and students, as well as observation and analysis of documents related to welfare-focused policies and programs. student. The program developed is a school principal leadership project plan through IHT activities. In this activity the teacher makes technology-based learning media with canva. The results of this study indicate that learning media made by teachers can improve student wellbeing which is indicated by 98.3% of students being enthusiastic about completing assignments, 97.5% of students being motivated to study at home or at school; 99.2% of students easier to understand learning material; 100% of students are proud of their results; 99.2% student achievement increased. School education management has an important role in improving student wellbeing. This research can provide insights for policy makers and education practitioners in designing strategies and programs that focus on student wellbeing e in schools